Structural and spectroscopic characteristics of thermally stable Eu3+ activated barium zinc orthophosphate phosphor for white LEDs. Issue 16 (November 2020) - Sahu, Mukesh K.; Kaur, Harpreet; Ratnam, B.V.; Kumar, J. Suresh; Jayasimhadri, M.
Abstract: Crystalline monoclinic phase of europium (Eu 3+ ) doped barium zinc orthophosphate [BaZn2 (PO4 )2 : BZP] phosphor has been synthesized via solid-state reaction technique. The phase purity, morphology and luminescent features of the as-synthesized phosphors have been examined using the results of X-ray diffraction (XRD), scanning electron microscopy (SEM) and photoluminescence (PL), respectively. The XRD results indicate pure phase formation of Eu 3+ doped BZP (BZP:Eu 3+ ) phosphor due to exact matching with the standard data of BZP. The SEM image specifies irregular shape of micro sized particles and non-uniform morphology. The BZP:Eu 3+ phosphor exhibits intense emission at 592 nm wavelength under ultraviolet (UV), near-UV and blue light excitations. The emission spectra disclose that the emission intensity improved with increase in Eu 3+ ions concentration up to 4.0 mol% and intensity decreases beyond it. The CIE coordinates (0.625, 0.363) calculated for the optimized BZP:Eu 3+ phosphor, which fall in the pure red region and close to commercially available red phosphor Y2 O2 S: Eu 3+ (0.647, 0.343). The PL intensity sustained up to 62.25% at 150 °C as compared to the intensity at room temperature indicating good thermal stability of BZP phosphor. All the above mentioned results signify the potential candidature of BZP:Eu 3+ phosphors for white light emitting devices.